Logistics - Gleissner, Harald; Femerling, J. Christian (Springer, 2013)
Globalization and Logistics are closely connected, just as Globalization and Academic Lecturing are. This poses new challenges in studying Logistics and makes textbooks in English an important tool in college and university curricula that deal with transportation, logistics, and supply chain management. The idea of offering a textbook in two languages was conceived after the success of the first volume of Logistik: Grundlagen – U¨bungen – Fallbeispiele, published in 2008. At that time, it was an early textbook primarily intended for students enrolled in bachelor degree programs in Logistics, and was extremely well received among academics and industry experts. Based on their own teaching experience, the authors later decided to prepare an English edition of the book to support international academic environments. In 2012, Gleissner and Femerling published a second edited volume in German, expanded by two additional chapters, “Logistics Infrastructure” and “Logistics and Finance,” which are also included in this English edition. In comparison to the German edition, the bibliography of this edition contains additional references concerning relevant US and British literature. The goal of the book is to present basic logistics concepts and principles in a format that is useful for students as well as practitioners dealing with logistic issues for the first time. The chapters therefore will help readers by providing: ¢ Learning objectives at the beginning of each chapter ¢ In-depth case studies ¢ Corporate applications in the industry ¢ End-of-chapter questions ¢ Chapter-specific references ¢ Chapter-specific recommendations for further reading For application and further information, readers are advised to consult Gleissner and Mo¨ller: Case Studies in Logistics from 2011.
Basics – Exercises – Case Studies